Total synthesis of the putative structure of xylarinol B - More, Atul A.; Ramana, Chepuri V. (Chemistry-An Asian Journal, 2014)
The total synthesis of the putative structure of xylarinolB is described and the need to revise its structure is demonstrated. The central benzoxepine skeleton was constructed by employing a cobalt-mediated bimolecular [2+2+2] Reppe-Vollhardt alkyne cycloaddition reaction.
Keywords: Chiral pool; cobalt; Natural products; structure elucidation; Total synthesis

Alkyne [2+2+2]-cyclotrimerization approach for synthesis of 6,7-cyclopropylallocolchicinoids - More, Atul A.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2016)
Employing a cobalt-catalyzed [2 + 2 + 2] alkyne cyclotrimerization as the final step, the short and efficient synthesis of cyclopropylallocolchicinoid and its analogues having functional group variations at C9 and/or C10 and C11 of ring C has been accomplished.

O-Quinone methides via oxone-mediated benzofuran oxidative dearomatization and their intramolecular cycloaddition with carbonyl groups: an expeditious construction of the central tetracyclic core of integrastatins, epicoccolide A, and epicocconigrone A - More, Atul A.; Ramana, Chepuri V. (Organic Letters, 2016)
The intramolecular cycloaddition of o-quinone methides (o-QMs) with a carbonyl group has been envisaged and executed successfully in the context of constructing the complex and rare [6,6,6,6]-tetracyclic core found in the integrastatins, epicoccolide A, and epicocconigrone A. These transient o-QMs were generated easily from the oxidative dearomatization of the corresponding C2-(aryl)benzofuran by employing Oxone in acetone-water at rt. The subsequent cydoaddition with the carbonyl (or conjugated olefin) present on the C2-aryl group was spontaneous.

Total synthesis of integrastatin B enabled by a benzofuran oxidative dearomatization cascade - More, Atul A.; Ramana, Chepuri V. (Organic Letters, 2016)
The first total synthesis of integrastatin B, a potent HIV-1 integrase inhibitor, has been accomplished in seven steps with a 17.9% overall yield employing easily accessible starting compounds. The Oxone-mediated oxidative benzofuran dearomatization cascade has been employed as the key skeletal construct to forge the central tetracyclic nucleus.